An Optimized Probe‐Based qPCR Assay for the Detection and Monitoring of the Invasive Lionfish (Pterois volitans) in the Atlantic - Katherine Viehl; Zain Khalid; Kathryn Greiner‐Ferris; Eli Taub; Pavithiran Amirthalingam; Girish Kumar; Victoria Marciante; Michelle R. Gaither (Environmental DNA)
ABSTRACT The Indo‐Pacific lionfish, Pterois volitans, is an invasive species in the western Atlantic. Since its introduction to Florida in the early 1980s, populations have surged with lionfish now found from North Carolina to Venezuela. As their range expands, these generalist predators threaten native fauna, and while they are primarily a marine species, their tolerance for low salinity conditions may allow them to expand into sensitive estuarine habitats undetected. Traditional approaches for tracking invasive species such as direct observation or trapping are impractical over large spatial scales, making environmental DNA (eDNA) an attractive alternative. Molecular assays, such as those employing quantitative polymerase chain reaction (qPCR), amplify low copy number DNA fragments in environmental samples and are increasingly employed as a complement to traditional methods for the detection of invasive species. Currently, there is one published PCR assay for the detection of lionfish eDNA. However, the specificity of this assay is unverified, and the critical performance parameters limit of detection (LOD) and limit of quantification (LOQ) have not been established. Here we evaluate the efficacy of this assay and show that it is likely to result in false negatives in the western Atlantic. As an alternative, we developed a new TaqMan probe‐based qPCR assay that is species‐specific for P. volitans and highly sensitive with a LOD of 12 copies per reaction and a LOQ of 598 copies per reaction. While our assay does not amplify the closely related P. miles, which was also introduced in the western Atlantic, the low prevalence of this species in the invasive population means our assay is effective for most monitoring purposes. We conclude that our assay is a robust method for the detection of lionfish and can be employed in any habitat, offering new opportunities for controlling the spread of invasive lionfish.